Benthobatis kreffti, krefft's blind numbfish - Pollom, R. (2020)
Krefft's Blind Numbfish (Benthobatis kreffti) is a small (to 30 cm total length) deep-water ray that occurs in the Southwest Atlantic from São Paulo to Rio Grande do Sul, Brazil. It is benthic on the continental slope at depths of 450–530 m. It is captured in deep-water demersal trawl fisheries, which developed rapidly in the 1990s and early 2000s in Brazil and remain intense and unmanaged. Overall, due to the level of unmanaged fishing pressure it is exposed to and its lack of refuge at depth, it is suspected that Krefft's Blind Numbfish has undergone a population reduction of 30–49% over the past three generations (15 years), and it is assessed as Vulnerable A2d.